Islamic Social Entrepreneurship-Based Community Empowerment Model through Waste Management at TPS-3R Tambakrejo Sidoarjo: A Literature Review - Anshori Anshori; Abu Yasid; Siti Musfiqoh; Iskandar Ritonga; Nurhayati Nurhayati (Journal of Innovative and Creativity, 2025)
This study evaluates the effectiveness of multi-stakeholder collaboration and develops strategies for community empowerment to enhance skills, optimize the economic value of waste, and foster environmental awareness in line with Islamic values. Using a qualitative descriptive approach based on a literature review and empirical analysis at TPS-3R Tambakrejo, Sidoarjo, data were collected from relevant scientific references and documentation studies, validated through source triangulation and extended observations. Findings show that the Islamic Social Entrepreneurship (ISE) approach increases community participation in waste management, opens local economic opportunities through recycling and value-added products, and promotes environmental education. Participatory management at TPS-3R fosters synergy among local actors, government, and communities rooted in Islamic principles. Key findings highlight the significant potential of household waste management to generate economic value, the absence of a structured Islamic-based empowerment model, and the need for integrative strategies involving education, training, and regulatory support. Islamic values serve as a moral force, strengthening awareness and participation in environmental preservation. In conclusion, waste management based on ISE is both an environmental solution and an innovative empowerment model. Through active participation, cross-sector collaboration, and the application of sharia principles, communities can independently manage waste while improving their living standards sustainably. This research provides a foundation for developing community-based policies and business models that integrate economic, spiritual, and socio-ecological dimensions.